Application of Hypnoteaching Method in Social Science Learning in Elementary School - Muslimin, Muslimin (Journal of Education and Computer Applications, 2025)
This study aims to describe the implementation and effectiveness of the hypnoteaching method in the IPAS (Science and Social Studies) learning process for fourth-grade students at UPT SD 214 in Pinrang Regency, as well as to explore students' responses toward the use of this method in IPAS learning. A descriptive qualitative approach was employed to elaborate on the application of the hypnoteaching method in IPAS instruction.Data collection was conducted through observation, interviews, and documentation. The findings revealed that the hypnoteaching method was successfully implemented by the teacher in a systematic manner across ten key aspects: intention and motivation, facing, leading, the use of positive language, giving praise, modeling, mastery of learning materials, enhancing students’ self-confidence, effective communication, and meaningful lesson closure. The teacher was able to create a learning environment that was comfortable, interactive, and conducive, thus supporting a more effective learning process. The application of the hypnoteaching method had a positive impact on increasing students’ learning motivation, self-confidence, and understanding of IPAS material. Students felt more at ease in a relaxed yet focused classroom atmosphere, allowing them to better follow the learning steps provided by the teacher.It is recommended that teachers continue to enhance their creativity in applying the hypnoteaching method, particularly by developing more innovative instructional strategies to support students' understanding of more complex IPAS topics. In addition, it is important for teachers to provide extra guidance for students who experience difficulties so that all learners can equally benefit from this method. Future studies are suggested to examine the implementation of this method on other IPAS topics to broaden the scope of its effective application.